Liver Stiffness Measurement by Vibration Controlled Transient Elastography Does Not Correlate to Hepatic Iron Overload in Children With Sickle Cell Disease. Issue 3 (April 2020) - Costa, Peter; Rudolph, Bryan; Kogan-Liberman, Debora; Manwani, Deepa; Silver, Ellen J.; Ovchinsky, Nadia
Abstract : Background: Children with sickle cell disease (SCD) are at risk of liver injury because of sickle cell hepatopathy and iron overload from chronic transfusions (CT). The authors examine the association between iron overload and liver stiffness measurement (LSM) by vibration controlled transient elastography (VCTE), which has been shown to correlate with fibrosis. Methods: Patients 21 years of age and less with SCD had VCTE performed; those who received CT underwent magnetic resonance imaging T2* for iron quantification. Results: The authors enrolled 42 patients, 17 (40%) of whom received CT. There was no difference in LSM between patients who underwent CT (5.5±1.5 kPa) and those who did not (5.2±2.3 kPa) ( P =0.923). There was no correlation between iron quantification and LSM ( r =−0.077, P =0.769). However, children 12 years of age and older had abnormal LSM when compared with a reference range ( P =0.013). Conclusion: VCTE is a noninvasive technology that is feasible in children with SCD. LSM values were elevated in older children but did not correlate with iron overload, suggesting that fibrosis may not be affected by iron overload alone. Though additional data are needed, LSM may be a useful test for the progression of liver disease in SCD regardless of iron burden.